Evaluating the sustainability of restaurant supply chains - Natapol Thongplew; Kanang Kantamaturapoj; Sittidaj Pongkijvorasin; Parcharapat Tawinnorppanan; Pia Laborgne (Journal of Agriculture, Food Systems, and Community Development)
This study investigates the sustainability of the organic restaurant supply chain, particularly in the Bangkok Metropolitan Area and Phuket in Thailand. The objectives of this study are to (1) establish sustainability criteria suitable for different contexts in urban Thailand, (2) evaluate the existing degree of sustainability in the organic restaurant supply, and (3) compare the interests and viewpoints of organic farmers, restaurateurs and consumers concerning supply chain sustainability. The scoping review was conducted to establish the sustainability criteria for the organic restaurant supply chain and implement these criteria in the context of urban Thailand. A total of 21 key informants underwent in-depth interviews to investigate their current sustainable practices as well as their perspectives regarding sustainability concerns. The sustainability criteria can be classified into four primary dimensions: economic; environmental and welfare; sociocultural; and governance. The findings of the study indicate that the organic restaurant supply chain has made substantial progress toward sustainability in the sociocultural and governance dimensions. However, the economics as well as the environmental and welfare dimensions have received lower levels of recognition by consumers.